Olfactory associations around space perception and the service received by members of a fund of employees in Manizales (2019)
This paper shows the results obtained in a research on sensory marketing and its influence on the shopping experience, which seeks to contribute knowledge to the sensory marketing field and its importance in making memorable experiences for the public. In this way it is intended to understand if a particular scent can be related to the experience of the service received in the facilities of fund of employees in Manizales through a quantitative-descriptive research with a quasi-experimental correlational scope. In the first week, 301 people who entered the facilities of the fund of employees without any scent scheme were interviewed. In the second week, an intervention was made: 301 surveys were collected from people who entered the same facilities, but this time with a scent scheme, and who rated the same variables. Surveys were systematized in a Microsoft Excel 2013® spreadsheet, and the statistical analysis was carried out with the IBM SPSS v. 2.1. software. Internal consistency was verified with Cronbach’s alpha of 0.856. Also, the population was characterized, and ordinal associations were established by the Gamma coefficient of Goodman and Kruskal. In addition, the possible associations were verified with a Chi-square test. One of the most important results of the study showed that smell stimulation can be linked in a positive way in the perception of the attention variables regarding service and cleaning.